Psychometric Properties of the Italian Version of the Young Schema Questionnaire L-3: Preliminary Results - Saggino, Aristide; Balsamo, Michela; Carlucci, Leonardo; Cavalletti, Veronica; Sergi, Maria R.; da Fermo, Giorgio; Dèttore, Davide; Marsigli, Nicola; Petruccelli, Irene; Pizzo, Susanna; Tommasi, Marco (Frontiers in Psychology, 2018)
Schema Therapy (ST) is a well-known approach for the treatment of personality disorders. This therapy integrates different theories and techniques into an original and systematic treatment model. The Young Schema Questionnaire L-3 (YSQ-L3) is a self-report instrument, based on the ST model, designed to assess 18 Early Maladaptive Schemas (EMSs). During the last decade, it has been translated and validated in different countries and languages. This study aims to establish the psychometric properties of the Italian Version of the YSQ-L3. We enrolled two groups: a clinical (n=148) and a nonclinical one (n=918). We investigated the factor structure, reliability and convergent validity with anxiety and depression between clinical and non clinical groups. The results highlighted a few relevant findings. Cronbach’s alpha showed significant values for all the schemas. All of the factor models do not seem highly adequate, even if the hierarchical model has proven to be the most significant one. Furthermore, the questionnaire confirms the ability to discriminate between clinical and non clinical groups and could represent a useful tool in the clinical practice. Limitations and future directions are discussed.